Handog kay Isabella - Gatmaitan, Luis P. (Chikiting books, 2013)
"A pognant story about the power of friendship and bayanihan, Handog kay Isabella teaches children the importance of helping each other, while sharing relevant information on how to avoid a common but dangerous illness."